Use of BRACU supplied cement and rebar in the work other than BOQ item no. 5.1, 7.1.2, 7.2.5. and 5.2, 7.1.4, 7.2.6 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the use of BRACU supplied cement and rebar works for BRACU new campus project.